Model Pembelajaran Berbasis Masalah dengan Langkah Penyelesaian Berdasarkan Polya dan Krulik-Rudnick Ditinjau dari Kreativitas Siswa - Utami, Rini (Delta Jurnal Ilmiah Pendidikan Matematika FKIP Universitas Pekalongan, 2013)
The objectives of this research are to investigate: (1) whether or not the problem-based learning model with the Polya-based solution steps results in a better learning achievement in Mathematics than that with the Krulik Rudnick-based solution steps; (2) whether or not the students with the high creativity have a better learning achievement in Mathematics than those with the medium creativity and whether or not the students with the medium creativity have a better learning achievement in Mathematics than those with low creativity; (3) which of the students with the high creativity, those with the medium creativity, and those with the low creativity have a better learning achievement in Mathematics when the problem-based learning model with the Polya-based solution steps is given; (4) which of the students with the high creativity, those with the medium creativity, and those with the low creativity have a better learning achievement in Mathematics when the problem-based learning model with the Krulik Rudnick-based solution steps is given; (5) which of the problem-based learning models each with the Polya-based solution steps and with the Krulik Rudnick solution steps results in a better learning achievement in Mathematics for the students with the high creativity; (6) which of the problem-based learning models each with the Polya-based solution steps and with the Krulik Rudnick-based solution steps results in a better learning achievement in Mathematics for the students with the medium creativity; (7) which of the problem-based learning models each with the Polya-based solution steps and with the Krulik Rudnick-based solution steps results in a better learning achievement in Mathematics for the students with the low creativity.This research used the quasi-experiment research with the factorial design of 2 x 3. The population of the research was the 4th-grade students of State Primary Schools in Bojong Sub-district, Tegal regency in the academic year of 2010/2011, which were 31 in the number of schools. The sampling was conducted by using the technique of stratified cluster random sampling. The samples in this research consisted of 212 respondents. The data were gathered through the instruments of learning achievement test in Mathematics and questionnaire on the students’ creativity level. Prior to their usefor gathering data, those instruments were tested. The validation of the test and questionnaire instruments was conducted by a competent person in validation, the reliability of the test was verified by using the KR-20 formula and the reliability of the questionnaire was verified by using the Alpha formula. In the prerequisite test on Analysis of Variance the Lilliefors test was used to verify the normality test while the Barlett test was used to verify the homogeneity test. With (α) = 0.05 the samples were obtained out of the population with normal and homogeneous distribution.The results of this research are as follows: (1) that the problem-based learning model with the Polya-based solution steps results in a better learning achievement in Mathematics that that with the Krulik Rudnick-based solution steps; (2) that there is no difference in the learning achievement in Mathematics among the students with the high, medium, and low creativities; (3) that the learning achievement in Mathematics of the students with the high creativity is equal to either that of those with the medium creativity or that of those with the low creativitywhen the problem-based learning model with the Polya-based solution steps is given; (4) that the learning achievement in Mathematics of the students with the high creativity is equal to either that of those with the medium creativity or that of those with the low creativity when the problem-based learning model with the Krulik Rudnick-based solution steps is given; (5) that the use of problem-based learning model with the Polya-based solution steps results in an equally good learning achievement in Mathematics to the use of that with the Krulik Rudnick-based solution steps among the students with the high creativity; (6) that the use of problem-based learning model with the Polya-based solution steps results in an equally good learning achievement in Mathematics to the use of that with the Krulik-Rudnick-based solution steps among the students with the medium creativity; (7) that the use of problem-based learning model with the Polya-based solution steps results in a better learning achievement in Mathematics than the use of that with the Krulik Rudnick-based solution steps.Keywords: problem-based learning model, the Polya-based solution steps, the Krulik Rudnick-based solution steps, the students’ creativities